Platform architectures: The structuration of platform companies on the Internet - Ulrich Dolata; Jan-Felix Schrape (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2022)
Today's internet is shaped largely by privately operated platforms of various kinds. This paper asks how the various commercially operated communication, market, consumption and service platforms can be grasped as a distinct organizational form of enterprise. To this end, we make a basic distinction between (1) the platform-operating companies as organizing and structuring cores whose goal is to run a profitable business, and (2) the platforms belonging to these companies as more or less extensive, rule-based and strongly technically mediated social action spaces. While platform companies are essentially organizations in an almost archetypical sense, the internet platforms they operate constitute socio-technically structured social, market, consumption or service spaces in which social actors interact on the basis of detailed and technically framed rules, albeit, at the same time, in a varied and idiosyncratic manner. The thesis of this paper is that the coordination, control and exploitation mechanisms characteristic of the platform architectures are characterized by a strong hierarchical orientation in which elements of co-optation and the orchestrated participation of users are embedded. In this hybrid constellation, the platform companies have a high degree of structure-giving, rulesetting and controlling power-in addition to exclusive access to the raw data material generated there. While this power may manifest, at times, as rigid control, direct coercion or enforceable accountability, for the majority of rule-obeying users it unfolds nearly imperceptibly and largely silently beneath the surface of a (supposed) openness that likewise characterizes the platforms as technically mediated spaces for social and economic exchange. – – Das heutige Internet wird durch privatwirtschaftlich betriebene Plattformen der unterschiedlichsten Art geprägt. Dieser Aufsatz fragt danach, wie sich diese verschiedenartigen kommerziellen Kommunikations-, Markt-, Konsum- und Serviceplattformen als distinkte Unternehmensform fassen lassen. Dazu wird eine basale Unterscheidung zwischen (1) den plattformbetreibenden Unternehmen als organisierenden und strukturierenden Kernen und (2) den ihnen gehörenden Plattformen als mehr oder minder ausgreifenden sozialen Handlungsräumen vorgenommen. Während sich Plattformunternehmen als Organisationen in einem geradezu klassischen Sinne darstellen lassen, konstituieren die von ihnen betriebenen Internetplattformen soziotechnisch strukturierte Sozial-, Markt-, Konsum- oder Serviceräume, in denen soziale Akteure zwar auf der Grundlage detailliert ausgestalteter und technisch eingefasster Regeln, aber zugleich variantenreich und eigenwillig interagieren. Die für solche Plattform-Architekturen charakteristischen Koordinations-, Kontroll- und Verwertungsmechanismen zeichnen sich durch eine starke hierarchische Ausrichtung aus, in die Elemente der Kooptation und des orchestrierten Mitwirkens der Nutzer eingelagert sind. Die Plattformunternehmen haben in dieser hybriden Konstellation ein hohes Maß an strukturgebender, regelsetzender und kontrollierender Macht - und verfügen überdies über den exklusiven Zugriff auf das dort produzierte Rohmaterial an Daten. Diese Macht äußert sich in vielen Fällen, aber längst nicht immer als rigide Kontrolle, als direktiver Zwang oder einklagbare Rechenschaftspflicht, sondern entfaltet sich für die große Zahl regel-konformer Nutzer weitgehend geräuschlos unter der Oberfläche einer (vermeintlichen) Offenheit, die die Plattformen als Markt- und Sozialräume auch auszeichnet.
Keywords: 300; Internetportal; E-Business; Netzwerkökonomik; Organisationsstruktur; Unternehmensorganisation